Mitigating Jahn–Teller effects by fast electrode kinetics inducing charge redistribution - Choi, Ahreum (2022)
Manganese hexacyanomanganates have attracted significant attention as promising cathode materials for sodium-ion batteries owing to the high theoretical capacity and low cost of Mn resources. Because of the strong Jahn–Teller effect, causing unstable local phase transition and distortion, the redox reactions of the high-spin state of Mn(III) are considered to be a conundrum. Herein, it is reported that the charge-redistribution mechanism of low-spin MnIII + high-spin MnIII → low-spin MnII + high-spin MnIV in manganese hexacyanomanganates can decrease unstable high-spin MnIII, leading to the mitigation of Jahn–Teller distortion. X-ray absorption near-edge spectroscopy and X-ray photoelectron spectroscopy suggest that the fast reaction rate activates charge redistribution. Moreover, different crystal structures, reported using post-mortem synchrotron X-ray diffraction analysis, confirm a large orthorhombic structure, thus verifying the presence of charge redistribution based on the superexchange rule. These results demonstrate that manganese hexacyanomanganate in an aqueous electrolyte can achieve long-term cyclability, thus paving the way for high-performance batteries.